A rare case of caesarean scar ectopic pregnancy: a case report - B., Hiremath P.; Anandabaskar, Vinothini; Arthi, Nivedhana; E., Rohini; R., Indu N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Scar ectopic pregnancy is a condition where the gestational sac implants into the previous caesarean scar site. Although it is a rare entity, its incidence is increasing due to rising rates of caesarean deliveries. Here authors report a case of caesarean scar ectopic pregnancy managed by laparotomy with caesarean scar ectopic excision following failed medical management. The patient recovered without any intraoperative or postoperative complications. An early diagnosis and management are vital in preventing maternal morbidity and mortality.